PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN ROLE MODEL TERHADAP INTENSI BERWIRAUSAHA BAGI MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS ISLAM RIAU - Ramadani Br Silalahi, Fitria; Eko Prabowo, Andri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of entrepreneurship education and Role Models on the entrepreneurial intention of students at the Faculty of Teacher Training and Education, Universitas Islam Riau. The research employs a quantitative approach using a correlational method. The research sample consists of 154 students selected through proportional random sampling techniques. Data were collected using questionnaires and analyzed through multiple linear regression using SPSS.The results indicate that entrepreneurship education has a positive and significant effect on students’ entrepreneurial intention. In addition, Role Models also have a positive and significant influence on entrepreneurial intention. Simultaneously, entrepreneurship education and Role Models have a significant effect on the entrepreneurial intention of students at the Faculty of Teacher Training and Education, Universitas Islam Riau.These findings suggest that students’ entrepreneurial intention is influenced by the implementation of practical entrepreneurship learning as well as the presence of inspirational Role Models. This study is expected to serve as a consideration for faculties and study programs in developing integrated entrepreneurship programs and as a reference for future research.